2017
DOI: 10.3892/etm.2017.5137
|View full text |Cite
|
Sign up to set email alerts
|

p63 inhibits CD44+/CD24‑ cell proliferation and chemoresistance in papillary thyroid carcinoma cells

Abstract: Thyroid cancer typically has a good prognosis; however, the risks of recurrence and chemoresistance associated with thyroid cancer remain a cause for concern. Papillary thyroid carcinoma (PTC) comprises 80% of all cases of thyroid carcinoma. A previous study reported that cluster of differentiation (CD) 44+/CD24− PTC cells may contribute to PTC recurrence and chemoresistance; however, the underlying molecular mechanisms remain elusive. In the present study, CD44+/CD24− cells were isolated from the TPC-1 PTC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Ahn et al [ 17 ] identified CD44+/CD24- cells in human papillary thyroid cancer cells, and the abundance of CD44+ cells exhibited a positive correlation with tumor aggressiveness. Guo et al [ 18 ] demonstrated that human papillary thyroid cancer cells expressing CD44+/CD24- exhibited enhanced proliferative capacity and resistance to 5-FU compared to CD44-/CD24- cells [ 18 ]. Ryu et al [ 11 ] showed that CD44+/CD24- was identified as an independent prognostic factor for PTC with a hazard ratio of 4.207.…”
Section: Discussionmentioning
confidence: 99%
“…Ahn et al [ 17 ] identified CD44+/CD24- cells in human papillary thyroid cancer cells, and the abundance of CD44+ cells exhibited a positive correlation with tumor aggressiveness. Guo et al [ 18 ] demonstrated that human papillary thyroid cancer cells expressing CD44+/CD24- exhibited enhanced proliferative capacity and resistance to 5-FU compared to CD44-/CD24- cells [ 18 ]. Ryu et al [ 11 ] showed that CD44+/CD24- was identified as an independent prognostic factor for PTC with a hazard ratio of 4.207.…”
Section: Discussionmentioning
confidence: 99%